Violent radical movements in the Arab world : the ideology and politics of non-state actors - Sluglett, Peter; Kattan, Victor (London [England] : I.B. Tauris, 2020)
"Violent non-state actors have become almost endemic to political movements in the Middle East and the Horn of Africa. This book examines why they play such a key role and the different ways in which they have developed. Placing them in the context of the region, separate chapters cover the organizations that are currently active, including: The Muslim Brotherhood, The Islamic State in Iraq and Syria, Jabhat al-Nusra, Hamas, Hizbullah, the PKK, al-Shabab and the Huthis. The book shows that while these groups are a new phenomenon, they also relate to other key factors including the 'unfinished business' of the colonial and postcolonial eras and tacit encouragement of the Wahhabi/Salafi/jihadi da'wa by some regional powers. Their diversity means violent non-state actors elude simple classification, ranging from 'national' and 'transnational' to religious and political movements. However, by examining their origins, their supporters and their motivations, this book helps explain their ubiquity in the region."--
Preface Victor Kattan -- Foreword: Peter Sluglett and the Study of the Modern Middle East Toby Dodge -- 1. Introduction: Violent Non-State Actors in the Arab World: some General Considerations -- Peter Sluglett -- 2. The Egyptian Muslim Brotherhood and Violence: Porous Boundaries and Context Khalid Hroub -- 3. The Islamic State in Iraq and Syria: Ideology vs. Context -- Hassan A. Barari -- 4. Between Religion, Warfare and Politics: the Case of Jabhat al-Nusra in Syria -- Mohamed-Ali Adraoui -- 5. The 2007 Hamas-Fatah Conflict in Gaza and the Israeli-American Demands -- Victor Kattan -- 6. Hizbullah and the Lebanese State: Indispensable, Unpredictable ? Destabilizing? -- Peter Sluglett -- 7. When the State becomes a Non-State: Yemen in the Huthi/Ali Abdullah Salih Alliance Daniel Martin Varisco -- 8. Violent Non-State Actors in Somalia: al-Shabab and the Pirates Afyare A. Elmi and Ruqaya Mohamed -- 9. ?Being in Time?: Kurdish Movement and Quests of Universal Hamit Borzolan -- Afterword Abdullah Baabood
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Online resource; title from PDF title page (EBSCO, viewed July 15, 2019).
Keywords: Radicalism -- Arab countries; Islam and politics -- Arab countries; Radicalisme; Middle Eastern history; Islam and politics; Radicalism; Arab countries